Pengaruh Dosis Pupuk Majemuk terhadap Pertumbuhan Stek Tanaman Bayam Brasil (Alternanthera sissoo) - Sumiahadi, Ade; Putra, Muhammad Rafi Wahyu (Fakultas Pertanian - UMJ, 2025)
Brazilian spinach (Alternanthera sissoo) is one of the vegetables introduced to several Southeast Asian countries, such as Indonesia. There are few scientific references on the optimal dose of fertilizer use, especially compound chemical fertilizers like NPK, on the growth of Brazilian spinach. This study aims to examine the effect of different doses of NPK on the growth of Brazilian spinach. The study was conducted from October 20, 2024, to January 24, 2025, in the researcher's home field located in Buaran Village, Serpong District, South Tangerang City. The research used a randomized block design (RBD) with 5 levels of NPK doses, namely 0 kg/hectare, 100 kg/hectare, 200 kg/hectare, 300 kg/hectare, and 400 kg/hectare. Each treatment level was repeated 5 times, and each experimental unit had 3 sample plants. The results showed that the tested doses of NPK compound fertilizers did not significantly affect all the observed growth variables of Brazilian spinach, which included the time of shoot emergence, number of shoots, number of leaves, leaf width, root length, root weight, consumption weight, and gross weight. The use of a planting medium mixture of soil, rice husk charcoal, and cow manure in a 1:1:1 ratio can support the growth of Brazilian spinach without the need for additional inorganic fertilization.